Current Accounts in a Currency Union - Decressin, Jorg (IMF Working Papers; Working Paper ;, 2009)
A fear about EMU was that in the absence of national currencies, country-specific shocks would result in greater current account divergences between member states. This paper finds that divergences across euro-area countries are smaller and have not risen relative to those across 13 other advanced economies with more flexible exchange rates. Also, the size of country-specific current account shocks in EMU countries is smaller and their persistence is greater than in the other advanced economies. However, these differences in current account dynamics do not appear related to different exchange rate dynamics.